Growth, characterization, and magnetic properties of a Li(Mn,Ni)PO4 single crystal - Wang, Kunpeng; Maljuk, Andrey; Blum, Christian G. F.; Kolb, Thomas; Jähne, Carsten; Neef, Christoph; Grafe, Hans-Joachim; Giebeler, Lars; Wadepohl, Hubert; Meyer, Hans-Peter; Wurmehl, Sabine; Klingeler, Rüdiger (Journal of crystal growth, 2014)
LiMn0.95Ni0.05PO4 single crystals have been grown for the first time by the travelling-solvent floating-zone method at low argon pressure. The grown sample exhibits large single crystalline grains as revealed by means of polarization microscopy, X-ray Laue back scattering, and single-crystal X-ray diffraction. The composition of the crystal was determined by Energy-dispersive X-ray (EDX) spectroscopy. LiMn0.95Ni0.05PO4 orders in an orthorhombic olivine-like structure as expected and phase purity was confirmed by powder X-ray diffraction. An oriented cuboid with size of 2.4×2.5×2.7mm3 along a, b, and c crystalline directions, respectively, was used for anisotropic magnetic measurements.
Im Titel ist die Ziffer "4" tiefgestellt
Available online 7 September 2013
Gesehen am 29.10.2020